The preventive effect of sulforaphane on liver injury in a non-heart-beating donor model (Annals of Medical Research, 2021)
Aim: In this preliminary study, we aimed to investigate the effect of sulforaphane (SFN) warm ischemia in a non-heart beat rat liver model (NHBD). Materials and Methods: Livers taken from NHBD 15,30,60 min after warm ischemia were stored up at University of Wisconsin solution for 5 h at 40C [cold storage (CS)] and were, then, exposed to 2 h of machine reperfusion (MRP) at 370C. In the study group, SFN 5 mg/kg was intraperitoneal given 30 min before the introduction of NHB. Firstly, we divided the rats into the control and SFN groups. Then, each group was divided into three groups (n=10 in each) including control I, II, III and SFN I, II, III groups (15-, 30-, and 60-min warm ischemia period, respectively).Control and study groups at the same time of ischemia were compared with each other in terms of lactate, AST, ALT, IL-6, TNF-α and morphologically.Results: In the group treated with SFN, AST, ALT, TNF-α, IL-6, and lactate levels were lower, compared to the control group. Histopathologically, Bcl-2 staining intensity and percentages of staining were statistically significant, compared to the control and study groups during 15-min warm ischemia. Although not statistically significant, the intensity and percentage of staining were higher at 30 min and identical at 60 min. Conclusion: Our study results suggest that, despite prolonged warm ischemia time, SFN can biochemically and morphologically protect the liver from the hazardous effects of ischemia reperfusion in an experimentally-controlled NHB in rats, indicating an increased utilization rate of NHBDs.
Keywords: Hepatic injury; NHBDs; organ preservation; sulforaphane; warm ischemia